India: The Emerging Global Power (American Journal of Management, 2021)
Using China as a benchmark, we assess the prospects and challenges facing India’s rise to global power status. The overall population size, growth and cohort composition favors rapid economic growth. India’s prospects are constrained by the failure to integrate women into the work force and the persistent religiously driven division. Consistent with China’s experience, increasing FDI and economic openness improves economic growth prospects; as would further moves towards a postmaterialist values. Of serious concern for both China and India are environmental challenges. The most prosperous regions will be seriously affected as forced migrations from neighboring even more affected societies increase. Barring unexpected events, India will likely reach parity with the US and China by 2050 and emerge as the dominant global power at the end of this Century.
Keywords: management; power; economic development; trade; finance; FDI; labor; environmental degradation; emerging markets; China; India